From the Editor’s Desk - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2019)
We are pleased to publish this December 2019 issue of the Grounded Theory Review, an online journal dedicated to supporting those who conduct classic grounded theory research. First developed by Glaser and Strauss in the early 1960s and further established by Glaser in the intervening years, classic grounded theory is a unique method of discovering never before recognized processes and patterns of human behavior. This issue includes three papers that discuss educational issues surrounding the method and four original classic grounded theories.